Effects of Video Task With a High-Level Exercise Illustration on Knee Movements in Male Volleyball Spike Jump - Liu, Xiangyu; Huang, Huiming; Li, Xiaohan; Li, Jianshe; Shi, Huijuan; Wang, Aiwen (Frontiers in Psychology, 2021)
Hazardous knee biomechanics, such as excessive knee affordance link with injuries in volleyball spike jumps (SPJs) and can be reconfigured by the enhancement of internal focus. The study aimed to explore the effects of video tasks illustrating a high-level SPJ on knee movement in the volleyball SPJ with 15 elite male volleyball athletes. This study investigated the knee movements in sagittal, coronal, and transverse planes before and after the video task in SPJ using one-dimensional statistical parametric mapping (SPM 1D) and discrete statistics. The SPM 1D indicated a larger knee flexion angle (31.17–73.19%, t = 2.611, and p = 0.012), increased knee flexion moment (19.72–21.38%, t = 0.029, and p = 0.029), and increased knee adduction angular velocity (49.07–62.64%, t = 3.148, and p = 0.004) after video task; alternatively, smaller knee external rotation angular velocity (45.85–49.96%, t = 5.199, and p = 0.017) and vertical ground reaction (vGRF) (3.13–5.94%, t = 4.096, and p = 0.014; 19.83–21.97%, t = 4.096, and p = 0.024) were found after the task. With discrete value statistics, the video task increased the peak of knee flexion angle while decreased the peak of extension moment, flexion moment, abduction moment, external moment, the first peak vGRF, and related loading rate. Conclusions: The results indicate that knee biomechanics in volleyball SPJ positively influenced by the video task. The task has the athletes control the knee movements more actively and improves the original hazardous movement strategies. Therefore, the video task presumably can abate the occurrence of knee injuries in volleyball SPJ. Further validation especially in the exercise effect is needed in the future.